From the ground up: Exploring the potential contribution of citizens' assemblies in radical food-system transformation - Inea Lehner; Johanna Jacobi; Philippe Mathys; Samira Amos (Journal of Political Ecology)
To contribute to food-system democratization and its transformation towards socio-ecological sustainability, various civil-society actors jointly organized a national citizens' assembly in Switzerland in 2022. For six months, 80 randomly selected Swiss residents learned about and deliberated on the food system. They then co-formulated and democratically approved 126 food-policy recommendations. Employing a political agroecology approach, this study entails two analyses that assess the transformative nature of these recommendations as well as six participants' development of "critical food-systems literacy", i.e., the ability to critically analyze the food system and take action to change it. Based on our findings, we propose that capitalist realism, or the acceptance of capitalism as the only viable political-economic system, must be countered to facilitate citizens' roles in envisioning radical transformation towards post-growth food systems.